A scene that desplaza (itself): Mapa Teatro's poetic and political experiences (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The present text discusses poetic and political experiences developed by the Colombian group Mapa Teatro in which space presents itself as a disruptive element and producer of desplazamientos. By making use of the notion of desplazamiento, the article seeks to put in evidence the multiple perceptual reconfigurations produced in propositions such as those involved in projects like C'úndua and Anatomia de la violencia en Colombia. As a common factor, through the different articulated spatialities, such creations enable the disarticulation, even if temporary, of certain structures linked to the impacts produced by the different forms of violence to which the territories named as Latin America are subjected.
Keywords: Colômbia; Desplazamiento; Space; Mapa Teatro